Chatgpt In Finance: Exploring Practical Uses, Emerging Challenges, and Mitigation Strategies - Sulaiman Taiwo Hassan; Abalaka, James Nda; Abdullahi Ya'u Usman (Systematic Literature Review Journal, 2025)
The advent of ChatGPT, a generative AI technology, has initiated significant transformation within the finance sector by allowing users to engage with digital systems using natural language. Despite its promising capabilities, integrating ChatGPT into financial operations introduces a host of ethical concerns that must be rigorously addressed to ensure its appropriate and conscientious use. This policy-focused article begins with a brief overview of ChatGPT’s utility in financial contexts and then examines the ethical dilemmas it raises. These include biased decision-making outputs, the risk of misinformation influencing financial outcomes, data privacy and security vulnerabilities, opacity in algorithmic processes, the displacement of human workers, and complex legal implications. We argue that financial entities adopting ChatGPT have a responsibility to develop and implement comprehensive strategies aimed at mitigating these ethical risks. In support of this goal, we outline policy recommendations designed to directly address these pressing issues. Ultimately, this article emphasizes the urgent need for a robust ethical framework to guide the deployment of ChatGPT in financial environments, ensuring that its implementation benefits both individuals and society. Furthermore, we highlight key areas for future research that can support ongoing efforts to integrate AI responsibly in finance.